Tele-Dentistry during Covid-19 Pandemic; Perceptions of Dentists in Pakistan - Salman Ashraf Khan, Naima Khalid, Obaid Bajwa, Amina Tariq, Zainab Naqvi (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study is to analyze the perception of Dentists in Pakistan towards Tele-Dentistry and its usefulness during Covid-19 pandemic. Materials & Methods: The study was conducted among general dentists of Lahore after taking approval from the Ethics and Research Committee of the institution. This descriptive cross-sectional study was completed over the period of three months. Non-probability snowball sampling technique was used. Results: The results revealed that most of the dentists (89.5%) perceived that Tele-Dentistry can be of help during COVID 19 Pandemic in Pakistan. Conclusion: Most of the dentists were aware of teledentistry, and its uses, advantages and disadvantages in Covid-19 pandemic. Keywords: teledentistry, Covid-19, dentistry, Lahore, perception, health care professionals